Kajian Hasil Pengujian X-Ray Diffraction (XRD) Dan Konstanta Dielektrik Membran Polimer Kitosan/PEG4000 dengan Lithium Triflat (LiCF3SO3) - Kartika - Sari; Agung Bambang Setio Utomo; Parmin Lumban Toruan; Ampala Khoryanton (Universitas PGRI Palembang, 2021)
Synthesis and testing of chitosan/PEG4000 solid electrolyte polymer membrane with LiCF3SO3 salt as a surfactant was carried out to determine crystalline size and type of structure using X-Ray Diffraction (XRD) and dielectric constant using Electrochemical Impedance Spectroscopy (EIS). The manufacture of chitosan/PEG4000 electrolyte polymer membrane with LiCF3SO3 salt using the solution casting method. The samples used in the XRD and EIS tests were in the form of solid electrolyte polymer membranes of chitosan, chitosan/PEG4000 and chitosan/PEG4000 with LiCF3SO3 salt. XRD test showed that the crystalline size of the chitosan, chitosan/PEG4000, and chitosan/PEG4000 electrolyte polymer membranes with LiCF3SO3 salt experienced a 2Î¸ angle shift and formed a semicrystalline phase. The peak intensity increase occurred after chitosan was added with PEG4000 with LiCF3SO3 salt. The crystalline size obtained for the electrolyte polymer membrane of chitosan, chitosan/PEG4000 and chitosan/PEG4000 salt LiCF3SO3 was 4,002 nm; 2,474 nm and 4,183 nm. Meanwhile, the type of structure produced by chitosan, chitosan/PEG4000 and chitosan/PEG4000 electrolyte polymer membranes with LiCF3SO3 salt is a semicrystalline phase. The dielectric constant for solid electrolyte polymer membranes of chitosan/PEG4000, and chitosan/PEG4000 with LiCF3SO3 salt are 3,4 and 16,6 x 103. XRD and EIS test results show that chitosan/PEG4000 polymer membrane with LiCF3SO3 salt as a surfactant can be applied as an alternative to solid electrolyte polymer secondary batteries.